Церкви Коропа - Кириєвський, В.Д. (Сіверщина в історії України, 2023)
У статті викладена історія церков містечка Коропа, колишнього адміністративного центру Коропської сотні Ніжинського полку. Наведені нові, раніше невідомі архівні документи, що були виявлені останнім часом. Також враховані новітні краєзнавчі публікації стосовно коропських церков. Стаття стане в нагоді для складання оновлених путівників до Коропа. The article describes the history of churches in the town of Korop, the former administrative center of the Korop Hundred of the Nizhyn Regiment. The article presents new, previously unknown archival documents that were discovered recently. Also taken into account are the latest local lore publications about the churches of Korop. The article will be useful for compiling updated guides to Korop. Even before the foundation of the Cossack hundred in Korop, in the 1630s, the first wooden Trinity Church was built in the middle of a sunny pine forest on the left bank of the Desna. Under the Cossacks, a fortress appeared in Korop with a length of ramparts of 744 fathoms. Within the fortress - «inside the city», according to the General Description of Left Bank Ukraine in 1767, there were already three churches. The new large Trinity Cathedral stood on Bazarnaia Square, near it is Assumption Church and at the exit from the fortress is the Transfiguration Church. Four more churches stood outside the fortress: two wooden churches - Mykhailivska and Vozdvizhenska and two stone ones - Voznesenska church and the Illina church located next to it on the second tier of the stone bell tower. Apparently, since that time, the legend about «The city of Korop - seven churches...» has been circulating in Korop. According to the description of the Novhorod-Siver Governorate in 1779-1781, there were 7 churches in the town of Korop. And at the end of the 18th century there were 8 churches and 7 belfries in Korop. The smaller number of bell towers is due to one common bell tower at the Ascension and Illina churches. They also had one parish - Voznesensky. The eighth church in Korop was the Pokrovska wooden church, built in 1796 within the boundaries of the former fortress, near its northern gate. Confessional information for 1796 of the parishioners of all seven churches has been preserved:1) Holy Life-giving Trinity, 2) Ascension of the Lord, 3) Dormition of the Mother of God, 4) Holy Archangel of Christ Michael, 5) Intercession of the Most Holy Mother of God, 6) Exaltation of the Holy Cross of God, 7) Transfiguration of the Lord. In 1902, a ninth Theodosius Church appeared in Korop along with the Trinity Church. The Trinity Church is listed in the insurance documents of 1910 as the Trinity-Theodosius Church. The number of parishes in Korop did not increase, it remained the same - seven, although there were already nine churches. Two of them - Illinska and Feodosiivska were heated by furnaces, they were warm in the cold, unheated Voznesenska and Troitska churches. Today, four stone churches have been preserved in Korop - Voznesenska (1756), Illinska (1764), Uspenska (1900) and Feodosiivska (1902).